Identification of Advertising Trends in The Mass Media and On the Internet Used by Modern Terrorism - Zelenkov, Mikhail Y.; Ponomarev, Vladimir G.; Gusev, Valery V.; Andreev, Anatoly N.; Makarov, Oleg N. (Cuestiones Políticas, 2020)
The authors have set themselves the goal of analyzing the mass media and coverage of terrorist attacks on the Internet, to assess their impact on the growing number of terrorists in the world based on this analysis. The methodological basis of this research is represented by the comprehensive approach, which allowed identifying and corroborating the need to restructure the media and the Internet to combat modern terrorism. The epistemological potential of the statistical and sociological methods used within quantitative and qualitative research makes it possible to properly interpret the results of scientific research devoted to the subject of analysis. The results suggest that current activity by the media and Internet users encourages the growth in the number of terrorist acts in the world and improves the efficiency of recruiting newcomers to terrorist organizations. Furthermore, optimal ways of restructuring social media and expanding the scope of control of the operation of the Internet without violating freedom of expression and the right of citizens to free access to information are discussed.